Tanggung Jawab Bank Kepada Nasabah Pasca Putusan Pengadilan Tindak Pidana Korupsi Pegawai Bank - Erna Susanti; Sulung Nugroho (Fakultas Hukum Universitas Mulawarman, 2024)
Customers are a crucial factor in the world of Banking. However, it is not uncommon for customers who have fully entrusted their confidence to the bank to become victims of the negligence of individuals within the bank. This research is conducted with the objective of ascertaining the nature of the bank's responsibility following the judgment of Court Decision Number 21/Pid.Sus-TPK/2019/PN Smr, in cases where customers incur losses due to criminal activities committed by bank employees. The protection of banks for Bank Customers is regulated under Law No. 10/1998 regarding Amendments to Law No. 7/1992 regarding Banking. Normatively, the bank is accountable in cases where losses occur as a result of criminal acts by internal individuals, not only the perpetrators but the bank is also jointly responsible in accordance with the explanation found in the Indonesian Civil Code (KUHPer), specifically Article 1367. Regarding customer protection, banks do not solely rely on civil law enforcement, as expected through sanctions and compensation claim mechanisms. Criminal law provisions also include regulations that can safeguard consumers, such as licensing and supervision mechanisms. Indirect protection afforded to customers in the event of criminal acts in the field of banking is established through a series of statutory regulations, such as Law No. 8/1999 regarding Consumer Protection, as well as regulations that can ensnare wrongdoers, such as Law No. 10/1998 regarding Banking, Law No. 11/2008 regarding Electronic Information and Transactions, and Law No. 20/2001 regarding the Eradication of Corruption. Meanwhile, the direct protection provided by banks to their customers involves meticulous planning based on the principle of prudence, as stipulated in Article 29 of Law No. 10/1998 regarding Banking.